Modeling the thermal performance of hybrid paraffin-air nanostructure in a heat sink: Effect of atomic ratio of Al2O3 nanoparticles - Wed khalid Ghanim; Rassol Hamed Rasheed; Ahmed Shawqi Sadeq; Mohammad N. Fares; Soheil Salahshour; Rozbeh Sabetvand (Case Studies in Chemical and Environmental Engineering)
This study investigates the effect of varying atomic ratios (1 %, 3 %, 6 %, and 10 %) of Al₂O₃ nanoparticles on the thermal performance of a hybrid paraffin-air nanostructure in a heat sink, using molecular dynamics simulations. The primary objective is to enhance the thermal properties of phase change materials for efficient energy storage, which is crucial for advancing thermal management systems. The purpose is to optimize nanoparticle concentration and assess how altering the atomic ratio of Al₂O₃ nanoparticles can improve thermal conductivity and heat flux within the phase change material matrix. The results demonstrate that after reaching equilibrium within 20 ns, the total energy of the atomic sample converges to −5990.70 eV, indicating stable atomic oscillations. Notably, increasing Al₂O₃ nanoparticle concentration to 3 % significantly improves the heat flux and thermal conductivity, reaching values of 354.11 W/m2 and 405.42 W/m·K, respectively. The radial distribution function analysis shows a decrease in the maximum peak to 3.49 at the 3 % concentration, suggesting that a higher concentration of oxygen atoms in the material could enhance thermal performance. Furthermore, the maximum temperature within the system increases to 934.17 K at the 3 % atomic ratio. The aggregation time at this concentration is 8.11 ns, which decreases to 6.83 ns at a 10 % atomic ratio, further supporting the detrimental impact of nanoparticle aggregation. Notably, a 3 % concentration is found to be optimal for improving performance. These findings show the critical role of Al₂O₃ nanoparticles in enhancing the thermal performance of phase change material-based systems, offering valuable insights into optimal nanoparticle concentration and aggregation for effective thermal management in energy storage applications.